IMPLEMENTASI KEBIJAKAN PENERBITAN IZIN MENDIRIKAN BANGUNAN DI KABUPATEN DONGGALA - Juti, Muhammad (Katalogis, 2021)
This research was conducted to describe the Implementation Policy for Issuance of Building Construction Permits in Donggala District whether it was in accordance with the expectations to be achieved based on the facts and facts in the field. By using a qualitative descriptive research method and based on the theory of Van Meter and Van Horn, the results obtained from the standard aspects and policy objectives already have Regional Regulations and Regents Regulations and Standard Operating Procedures (SOP) as guidelines for implementation. From the aspect of resources not yet optimal where there is still a lack of competent human resources and facilities and infrastructure in its operations. From the aspect of implementation activities carried out socialization by both the Investment and One-Stop Services and the PUPR Office by coordinating with other relevant agencies. From the characteristic aspects of implementing agents, they have a commitment and responsibility for their respective functions. From the social, economic and political aspects in general it has not fully supported the implementation of the policy. And from the disposition aspect where the trend of the implementor is not optimal where the response and understanding of the agent of the implementor is not maximal. In general, the implementation of the issuance policy has not been maximized because several aspects studied have not been optimal in its implementation. The six aspects studied are related to each other and cannot be separated so that to maximize the implementation of a policy all aspects must be in line. It is expected that theoretically this research can contribute to development. Where the results of this study are expected to provide feedback to the Donggala District Government along with related elements, so that the Donggala District Government and various parties, both researchers from universities, DPRDs, community leaders, NGOs, and Entrepreneurs are looking for the policy format needed to become a reference government activities in the service of issuing building permits that are more efficient, responsive and accountable.